2011
DOI: 10.1051/epjap/2011110120
|View full text |Cite
|
Sign up to set email alerts
|

About the transparent electrode of the organic photovoltaic cells

Abstract: Abstract. Electrodes and the nature of their contact with organic materials play a crucial role in the realization of efficient optoelectronic components. Whether the injection (organic light emittin g diodesOLEDs) or collection (organic photovoltaic cells -OPV cells) of carriers, contacts must be as efficient as possible. To do this, it is customary to refer to electrode surface treatment and / or using a buffer layer all things to optimize the contac t. Efficiency of organic photovoltaic cells based on organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The thickness of such metal oxide is important. A too thin ABL leads to inhomogeneous properties at the interface anode/ED by incomplete surface coating [19], while a too thick layer increases the serial resistance (Rs) and therefore reduces Jsc and FF. We have already shown that, in the experimental conditions used in this work, the optimum thickness of the MoO 3 ABL is 3 nm [20].…”
Section: Characterization Of a Photovoltaic Cell Ablsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness of such metal oxide is important. A too thin ABL leads to inhomogeneous properties at the interface anode/ED by incomplete surface coating [19], while a too thick layer increases the serial resistance (Rs) and therefore reduces Jsc and FF. We have already shown that, in the experimental conditions used in this work, the optimum thickness of the MoO 3 ABL is 3 nm [20].…”
Section: Characterization Of a Photovoltaic Cell Ablsmentioning
confidence: 99%
“…For BrPhPZn layers thick of 50 nm it is observed that the Jsc and Voc values are low, and they increase gradually as the film thickness diminishes. This response could be related to the low conductivity and hole mobility of the compound [19].…”
Section: Thickness Of the Brphpzn Filmmentioning
confidence: 99%